2021
DOI: 10.1111/imr.12986
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast pathology in inflammatory joint disease

Abstract: In this review, we highlight new approaches and applications of single-cell profiling techniques 1,2 and how these data are leading to unique insights into the phenotypic and functional heterogeneity of fibroblasts in the joint. 3 Finally, we will discuss how defining this previously underappreciated fibroblast heterogeneity in rheumatoid arthritis (RA) is leading to the identification of pathological fibroblast cell states that could be therapeutically targeted in inflammatory joint disease. 4 | Rheumatoid ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 200 publications
0
24
0
Order By: Relevance
“…Fibroblasts are the main component of the inner wall of the joint cavity called the synovium. During joint inflammation, fibroblasts promote the recruitment and retention of inflammatory cells by producing inflammatory mediators at pathogenic levels, thereby contributing to disease pathology [ 25 ]. The MH7A synovial fibroblast cell line used in this experiment is a chemically treated cell line extracted from the synovium of a female RA patient using SV40 T antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts are the main component of the inner wall of the joint cavity called the synovium. During joint inflammation, fibroblasts promote the recruitment and retention of inflammatory cells by producing inflammatory mediators at pathogenic levels, thereby contributing to disease pathology [ 25 ]. The MH7A synovial fibroblast cell line used in this experiment is a chemically treated cell line extracted from the synovium of a female RA patient using SV40 T antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Because recent studies using single-cell RNA-seq (scRNA-seq) on RA synovium identified specific fibroblast subsets with critical roles in RA pathogenesis 13 , 14 , 16 , 29 , we applied modular analysis based on scRNA-seq fibroblast subsets 14 and orthogonal validation by multiplex immunofluorescence, and identified an association between DKK3 + fibroblasts and refractoriness. DKK3 encodes Dickkopf3, a negative regulator of beta-catenin that has been shown to promote aggressive behaviour in cancer-associated fibroblasts 30 , although the exact function of DKK3 + fibroblasts in RA remains to be established 31 . Furthermore, DSP revealed specific upregulation of genes in the sublining of refractory patients encoding for the fibroblast marker FAP, which has been linked with RA pathogenesis 16 , while other markers consistently modulated across all regions included CCL13 encoding for the monocyte-attracting chemokine MCP-4, which has been shown to activate synovial fibroblasts 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Remodeling the epigenome is likely underlying these stable pathologic changes in SF gene expression and function (38,39). For instance, DNA methylation patterns in SFs from RA patients are very distinct from those in osteoarthritis and SFs from non-inflamed individuals (40).…”
Section: Discussionmentioning
confidence: 99%